Effect of Cholic Acid on Fetal Cardiac Myocytes in Intrahepatic Choliestasis of Pregnancy - 高慧 陈莉娟 罗青清 刘晓夏 胡颖 于利利 邹丽 (Journal of Huazhong University of Science and Technology. Medical sciences, 2014)
This study examined the effect of cholic acid （CA） on cultured cardiac myoeytes （CMs） from neonatal rats with an attempt to explore the possible mechanism of sudden fetal death in intra- hepatic cholestasis of pregnancy （ICP）. Inverted microscopy was performed to detect the impact of CA on the beating rates of rat CMs. MTT method was used to study the effect of CA on the viability of CMs. CMs cultured in vitro were incubated with 10 ~maol/L Ca2＋-sensitive fluorescence indicator fluo-3/AM. The fluorescence signals of free calcium induced by CA were measured under a laser scanning confocal microscope. The results showed that CA decreased the beating rates of the CMs in a dose-dependent manner. CA could suppress the activities of CMs in a time- and dose-dependent manner. CA increased the concentration of intracellular free calcium in a dose-dependent manner. Our study suggested that CA could inhibit the activity of CMs by causing calcium overload, thereby leading to the sudden fetal death in ICP.